(untitled) (Journal of the College of Basic Education, 2024)
The study of Yemeni personalities and groups in history is one of the studies that gives the individual a role in writing, and the subject of the study, Sultan Abdul Hamid II, is one of the important topics that sheds light on his private life and its impact on the final exam, Mike, and the accompanying events of its work in his politics, since no one knew how to study it academically, as He was raised as an orphan, and lived in a state of isolation, introversion, suspicion, fear, and distrust of others. He was influenced by major religious figures, and was able to rule the Sultanate for thirty years.